DISCURSIVE CATEGORIES OF THE ENGLISH DIPLOMATIC DISCOURSE - Кащишин, Наталія (Current Issues of Foreign Philology, 2021)
The author attempts to describe the English diplomatic discourse through the prism of its discursive categories. Polemical views concerning the interpretation of the concept of a discursive category are presented. The classifications of the categories of discourse are analysed. The concept of a discursive category is specified. The taxonomy of discursive categories is suggested and the basic discursive categories of the diplomatic discourse are singled out. The description of such categories as modality, emotiveness, point of view, event, which are the backbone of the categorial grid of the English diplomatic discourse, is suggested. In this way an attempt to define the categorial grid of the diplomatic discourse as an institutional type of discourse is carried out. It is found out that of particular importance to diplomatic communication is the category of modality and the category of event. The author gives a detailed review of the interpretations of modality by different scholars. The main language means that often serve to express the categories constituting the core of the categorial taxonomy of the diplomatic discourse are presented.